'Small cost to pay for peace of mind': Women's experiences with non‐invasive prenatal testing. (6th February 2019) - Bowman‐Smart, Hilary; Savulescu, Julian; Mand, Cara; Gyngell, Christopher; Pertile, Mark D.; Lewis, Sharon; Delatycki, Martin B.
Abstract : Background: Non‐invasive prenatal testing (NIPT) has been available in Australia on a user‐pays basis since 2012. Since its introduction, it has grown in popularity as a screening method for fetal aneuploidy and may become publicly funded. Aims: To assess the motivations and experiences of women who have undergone NIPT in a user‐pays system in Australia. Materials and methods: One thousand women who had undergone NIPT through the Victorian Clinical Genetics Services in Melbourne, Australia were contacted and asked to complete a mixed‐methods survey. The number of eligible responses received was 235. Quantitative data analysis was performed in STATA IC 15.1, and qualitative data were examined using content analysis. Results: Women reported generally positive experiences with NIPT and 95% of respondents indicated they would undergo NIPT in a future pregnancy. Most respondents received a low‐risk result, with 2.2% receiving a high‐risk result. Respondents viewed NIPT favourably compared to invasive testing and cited reassurance as a key reason they sought it. However, a small minority of women reported negative experiences with the testing process. Women were also supportive of NIPT becoming publicly funded, with 93% of respondents indicating support. Pre‐ and post‐test counselling were identified as possible areas for improvement to ensure informed consent. Conclusion: In support of the existing literature, these results indicate that Australian women generally report positive experiences with NIPT. As NIPT becomes more common, with possible integration into public healthcare, further qualitative research would be valuable to examine the motivations and experiences of women undergoing NIPT.